A Role for Glucocorticoids in Thymic Involution? - Jan Wiegers, G.; Tischner, Denise (Current Immunology Reviews (Discontinued), 2011)
Aging of the immune system is characterized by a decline in adaptive immunity that leads to immune dysfunction in the elderly. The striking involution of the thymus with age is thought to be mainly responsible for the loss of immunocompetence. This involution process has been attributed not only to changes in the production of sex hormones but also to intrinsic defects in aged progenitor T-cells. Counteracting thymic involution is expected to contribute to restoration of immune function in the elderly. Here, we focus on recent evidence that glucocorticoid hormones might fulfil such a role.
Keywords: pregnenolone